2015
DOI: 10.2298/vsp140624078m
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-associated urinary tract infection in a surgical intensive care unit

Abstract: The risk factors and causative microrganisms considering CAUTIs in the SICU must be considered in of planning CAUTIs prevention in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…Nine studies (Barbadoro et al., ; Gillen et al., ; Hagerty et al., ; Kabbani et al., ; Kim et al., ; Lee et al., ; Mladenović et al., ; Talaat et al., ; Vincitorio et al., ) that included a total of 565 patients with CAUTI and 8,070 patients without CAUTI were included in the analysis of gender and CAUTI risk. The pooled results demonstrated that female gender was associated with an increased CAUTI incidence (OR = 2.01, 95% CI, 1.64–2.14, p < 0.05, Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies (Barbadoro et al., ; Gillen et al., ; Hagerty et al., ; Kabbani et al., ; Kim et al., ; Lee et al., ; Mladenović et al., ; Talaat et al., ; Vincitorio et al., ) that included a total of 565 patients with CAUTI and 8,070 patients without CAUTI were included in the analysis of gender and CAUTI risk. The pooled results demonstrated that female gender was associated with an increased CAUTI incidence (OR = 2.01, 95% CI, 1.64–2.14, p < 0.05, Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies (Talaat et al., ; Vincitorio et al., ) compared the hospital length of stay (LOS) between CAUTI and No CAUTI groups. And another four studies (Kabbani et al., ; Lee et al., ; Mladenović et al., ; Talaat et al., ) compared the ICU LOS between these two groups. The pooled data suggested that CAUTI risks were higher in those with a longer hospital LOS (MD of +4 days, 95% CI, 2.64–6.42, p < 0.05, Figure ) and ICU LOS (MD of +12 days, 95% CI, 3.98–21.24, p = 0.004, Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…18,[22][23][24][25] However, unlike the study of Mladenovi et al no difference in rate of CAUTIs was observed among patients of different age group. 21 We identified Candida spp. as the most frequently Abbreviation: SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Notable urinary pathogens causing UTI include Gram-negative rods (Escherichia coli, Citrobacter spp, Enterobacter spp), Gramnegative cocci (Neisseria gonorrheae), Grampositive cocci (Staphylococcus aureus, Staphylococcus saprophyticus), and other pathogens such as Candida albicans, and Chlamydia trachomatis (5,6). This risk of UTI is high in women, infants, elderly, and people with spinal cord injuries, urinary catheters, diabetes, immunodeficiency, and underlying urologic abnormalities (7,8,9,10).…”
Section: Introductionmentioning
confidence: 99%